The 1945 World Order – Process with «Open» Continuation - V. T. Yungblud (Vestnik MGIMO-Universiteta, 2020)
The Yalta-Potsdam system of international relations, established by culmination of World War II, was created to maintain the security and cooperation of states in the post-war world. Leaders of the Big Three, who ensured the Victory over the fascist-militarist bloc in 1945, made decisive contribution to its creation. This system cemented the world order during the Cold War years until the collapse of the USSR in 1991 and the destruction of the bipolar structure of the organization of international relations. Post-Cold War changes stimulated the search for new structures of the international order. Article purpose is to characterize circumstances of foundations formation of postwar world and to show how the historical decisions made by the leaders of the anti-Hitler coalition powers in 1945 are projected onto modern political processes. Study focuses on interrelated questions: what was the post-war world order and how integral it was? How did the political decisions of 1945 affect the origins of the Cold War? Does the American-centrist international order, that prevailed at the end of the 20th century, genetically linked to the Atlantic Charter and the goals of the anti- Hitler coalition in the war, have a future?Many elements of the Yalta-Potsdam system of international relations in the 1990s survived and proved their viability. The end of the Cold War and globalization created conditions for widespread democracy in the world. The liberal system of international relations, which expanded in the late XX - early XXI century, is currently experiencing a crisis. It will be necessary to strengthen existing international institutions that ensure stability and security, primarily to create barriers to the spread of national egoism, radicalism and international terrorism, for have a chance to continue the liberal principles based world order (not necessarily within a unipolar system). Prerequisite for promoting idea of a liberal system of international relations is the adjustment of liberalism as such, refusal to unilaterally impose its principles on peoples with a different set of values. This will also require that all main participants in modern in-ternational life be able to develop a unilateral agenda for common problems and interstate relations, interact in a dialogue mode, delving into the arguments of opponents and taking into account their vital interests.